Transarterial Treatment with Onyx of Intracranial Dural Arteriovenous Fistula with Cortical Drainage in 17 Patients - Maimon, S. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: Intracranial DAVFs with cortical venous drainage have a high tendency to bleed. Complete closure of these lesions is essential to prevent clinically deleterious events. We describe our experience using Onyx in an arterial approach for treatment of DAVFs in 17 patients. MATERIALS AND METHODS: Between 2006 and 2010, we used Onyx for performing transarterial embolization in 17 patients with intracranial DAVFs and cortical venous drainage. Clinical assessment was performed before and after every treatment at discharge and at follow-up. Fourteen patients underwent follow-up MR imaging and MRA, 8 of them also underwent follow-up diagnostic angiography. RESULTS: Fifteen patients (88%) underwent 1 procedure. Complete obliteration by embolization with Onyx was achieved in 16 patients (94% acute obliteration). The mean amount of Onyx injected was 2.3 mL (range, 0.4–4.8 mL). The sole technical complication was an embolus to a branch of the MCA, which was resolved by intra-arterial tPA injection. A clinical complication of transient trochlear nerve palsy in the same patient due to mass effect of Onyx resolved spontaneously within 3 months. CONCLUSIONS: Intra-arterial embolization of cranial DAVFs with cortical venous drainage by using Onyx results in a high rate of complete obliteration (94%) with low morbidity (6%). Follow-up DSA in 8 patients revealed no evidence of reopening.